My crazy character - Sojini, Lungile (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2020)
My thesis is a metafictional novella. I am interested in fictionalising the processes that writers use when they sit down to plan, write and publish novels. Metafiction interests me because it breaks from the traditional way of writing fiction, particularly with regards to the appearance of the author in the fictional world created. Devin Gribbons's metafictional story (titled A Short Story), in the anthology of innovative writing, 30 Under 30, was my inspiration for developing the metafictional approach to novella length. Fyodor Dostoevsky's Notes from Underground, Chief Fagunwa's Forest of a Thousand Daemons, and Charles Bukowski's autobiographical Ham on Rye, have for varying reasons, all influenced this writing.
Keywords: South African fiction (English) -- 21st century